2008
DOI: 10.1007/s00360-008-0262-z
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants in eggs of great tits Parus major from Chernobyl and hatching success

Abstract: Antioxidants are powerful protectors against the damaging eVects of free radicals that constitute the inevitable by-products of aerobic metabolism. Growing embryos are particularly susceptible to the damaging eVects of free radicals produced during rapid growth, and mothers of many species provide protection against such damage by allocating antioxidants to their eggs. Birds living in radioactively contaminated areas use dietary antioxidants to cope with the damaging eVects of radiation, but females also alloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
30
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 24 publications
(31 reference statements)
5
30
4
Order By: Relevance
“…Each observation represents an estimate for an urban and a rural population of a single species. The line shows similar concentrations in the two environments Møller et al (2005Møller et al ( , 2008 showed for birds in Chernobyl that levels of vitamin E were positively correlated with the frequency of sperm with normal morphology and hatching success. Here we tested the prediction that liver antioxidants predicted risk of predation by investigating carotenoids and vitamin E in birds captured by cats and in conspeciWcs that had died for other reasons.…”
Section: Discussionsupporting
confidence: 63%
“…Each observation represents an estimate for an urban and a rural population of a single species. The line shows similar concentrations in the two environments Møller et al (2005Møller et al ( , 2008 showed for birds in Chernobyl that levels of vitamin E were positively correlated with the frequency of sperm with normal morphology and hatching success. Here we tested the prediction that liver antioxidants predicted risk of predation by investigating carotenoids and vitamin E in birds captured by cats and in conspeciWcs that had died for other reasons.…”
Section: Discussionsupporting
confidence: 63%
“…In addition, it suggested that the population decline is due to lower fecundity and/or lower fledging rate, as demonstrated by a decrease in the proportion of juveniles at higher levels of radiation exposure. This result is consistent with the demonstrated decline in fertility, reproductive function and parental care that we have shown in Chernobyl in the barn swallow as well as in other species35404142.…”
Section: Discussionsupporting
confidence: 92%
“…3 Relationship between average ambient temperature of a 3-day period preceding laying and egg mass (g) of Great Tits in the Pilis Mountains. Average ambient temperature values were log-transformed 2011), but higher than that found in Great Tit eggs in Sweden (Isaksson et al 2008), France, and Ukraine (Møller et al 2008). Tocopherol concentration was similar to the values found in the Czech population of Great Tits (Remeš et al 2011), but higher than that found in Great Tit eggs in Estonia (Hõrak et al 2002), France, and Ukraine (Møller et al 2008).…”
Section: Discussionmentioning
confidence: 58%
“…Average ambient temperature values were log-transformed 2011), but higher than that found in Great Tit eggs in Sweden (Isaksson et al 2008), France, and Ukraine (Møller et al 2008). Tocopherol concentration was similar to the values found in the Czech population of Great Tits (Remeš et al 2011), but higher than that found in Great Tit eggs in Estonia (Hõrak et al 2002), France, and Ukraine (Møller et al 2008). These differences show that food and dietary antioxidant availability in different types of habitats may considerably influence the antioxidant concentration of the egg yolks of wild birds.…”
Section: Discussionmentioning
confidence: 58%